PENINGKATAN HASIL BELAJAR SISWA KELAS VI SDN 1 NYALINDUNG KECAMATAN CIPATAT MELALUI MEDIA PEMBELAJARAN PADA MATA PELAJARAN BAHASA INDONESIA TAHUN AJARAN 2012-2013 - -, Resmini (PEDAGOGIA, 2016)
This study aims to improve the ability of students in learning Indonesian. The study conducted in Class VI SDN 1 Nyalindung District Cipatat West Bandung district on October 2, 2012 until October 22, 2012. Learning Model through the medium of learning. It is expected to use the model of the approach and direction of research will increase student learning outcomes and can apply and enrich vocabulary Indonesian well and correctly. The successful implementation of these improvements, the learning process, is planned, observed, and evaluated the results in the two study cycles each class 3 meetings. From the results of the implementation study classes in two cycles can be concluded that the model learning through Media Learning can improve learning outcomes and can apply the vocabulary properly in a sentence coherently. It can see the results of the evaluation of the first cycle, the average value achieved by students is 64.75 percent increase to 72.00.Kemudian completeness of sixth-grade students increased from 54% increased to 64.75% in the first cycle, also on the second cycle increased to 72%. The learners are satisfied and motivated to apply it in accordance with time provided.Â Keywords: The mindset of language, learning approach through the medium of learning